2012
DOI: 10.1016/j.rbp.2012.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Homozygosity for the APOE E4 Allele is Solely Associated with Lower Cognitive Performance in Brazilian Community-dwelling Older Adults – The Bambuí Study

Abstract: The APOE E4 allele was observed to have a dramatic effect on cognitive impairment, especially in homozygotes, which comprised approximately 2% of the population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The human ApoE2, ApoE3, and ApoE4 alleles have worldwide frequencies of 8.4%, 77.9%, and 13.7%, respectively [16]. However, while the frequency of ApoE4 was 13.5% in an elderly Brazilian population [9], it was 8.7% in a community-dwelling Korean population [17]. Differences in the study subjects and methods used for ApoE genotyping may also have contributed to the variations in the reported prevalence rates of the ApoE4 genotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The human ApoE2, ApoE3, and ApoE4 alleles have worldwide frequencies of 8.4%, 77.9%, and 13.7%, respectively [16]. However, while the frequency of ApoE4 was 13.5% in an elderly Brazilian population [9], it was 8.7% in a community-dwelling Korean population [17]. Differences in the study subjects and methods used for ApoE genotyping may also have contributed to the variations in the reported prevalence rates of the ApoE4 genotype.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to nondemented people, there is controversy about the association between risk factors for cognitive impairment and ApoE4. Some studies [7][8][9] have observed ApoE4-related deficits in cognitive performance, while control studies [10,11] have found no difference in the prevalence of ApoE4 between healthy controls and SCD groups.…”
Section: Introductionmentioning
confidence: 99%
“…It is also important to point out that in this same population, the presence of ε4 allele is associated with lower cognitive performance 43 , but we considered cognitive functioning to be a confounding factor. In addition, it has been shown that the cognitive deficit is more strongly associated with the decline of IADL (which was not associated with apoE genotypes in this study) compared with BADL and mobility 18 , showing that other factors may modulate this association, besides cognitive decline 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Several other studies found ApoE∊4 could significantly affect MMSE score. 18,19 The MMSE is a roughly cognitive test used to screen dementia; it can’t measure the cognitive function accurately. Kim et al 20 examined 215 Korean individuals who were 65 years or older and didn’t find a significant effect of ApoE∊4 on MMSE score.…”
Section: Discussionmentioning
confidence: 99%